PENGARUH DIAMETER MAIN JET TERHADAP KINERJA MESIN PENGGERAK KAPAL NELAYAN SKALA KECIL - Nugroho, Agung; Arifin, Syamsul; Wahid, Muhammad Abdul (Otopro, 2024)
Environmental pollution caused by exhaust gases from two-stroke outboard engines, known for their high fuel consumption, is a significant issue for small-scale fishermen. This study aims to optimize fuel consumption and engine performance by examining the effect of main jet diameter on a 40 Hp two-stroke outboard engine. The experimental method was employed with three main treatments: main jet #150, #145, and #135. Testing was conducted by measuring fuel consumption at various engine speeds (rpm) – maximum, medium, and minimum – as well as the resulting boat speed. The results showed that using a larger main jet (#150) produced lower rpm and boat speed but higher fuel consumption. Conversely, the main jet #135 yielded higher rpm and boat speed with more efficient fuel consumption. However, potential long-term engine damage was indicated with the use of main jet #135. In conclusion, the main jet #145 is  considered optimal for normal operating conditions, offering a balance between engine performance and fuel efficiency.